Recovery of Slow-Release Fertilizer from Tofu Wastewater via Magnesium Ammonium Phosphate (Struvite) Precipitation: Effect of pH and Molar Ratio - Raudhatul Ulfa; Firda Tirta Yani; Gita Nurma Yunita; Faisal Faisal; Misbul Hadi; Chindy Mauliza Duana; Wiza Ulfa Fibarzi (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2026)
Tofu wastewater contains high concentrations of phosphate (PO43−) and ammonium (NH4+), which can cause eutrophication if discharged without proper treatment. One promising method for nutrient recovery and wastewater remediation is struvite (MgNH4PO4·6H2O) precipitation, which simultaneously removes phosphate and produces a slow-release fertilizer. This study investigates the effect of pH variation (8, 9, and 10) and molar ratios of Mg2+:NH4+:PO43− (1:1:1, 4:1:1, and 1:4:1) on phosphate removal efficiency, product yield, and morphological characteristics of the formed crystals. Experiments were conducted with a reaction time of 60 minutes under controlled pH conditions. The results revealed that both pH and molar ratio significantly affected the phosphate precipitation process. The highest phosphate removal efficiency of 89.94% was obtained at pH 9 with a 4:1:1 molar ratio, indicating that excess Mg2+ under moderately alkaline conditions favored struvite formation. In contrast, the highest calculated product yield was observed at pH 8, showing that the condition giving maximum mass-based recovery was not identical to the condition giving maximum phosphate removal efficiency. At pH 10, phosphate removal efficiency decreased, most likely due to the formation of competing Mg(OH)2 precipitates, which reduced the availability of free Mg2+ for struvite crystallization. Scanning Electron Microscope (SEM) and X-ray Diffraction (XRD) analysis showed that the struvite crystals exhibited block-like morphologies with irregular surfaces and an average size of 20–50 μm. Although nutrient-release kinetics were not directly measured in this study, the observed crystal size may influence dissolution behavior based on the surface-area effect reported in the literature, supporting the potential application of the recovered struvite as a slow-release fertilizer. Overall, the findings demonstrate that pH 9 and the molar ratio of 4:1:1 represent the optimal conditions for struvite production from tofu wastewater, offering an environmentally sustainable approach to nutrient recovery and contributing to circular economy practices in agriculture.